2014
DOI: 10.5897/jtehs2014.0312
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating potential and antioxidant properties of aqueous seed extract of Leea guineensis against dichlorovos-induced toxicity in Wistar rats

Abstract: This work was carried out to access the mitigating potential of Leea guineensis aqueous seed extract against dichlorovos (DDVP)-induced toxicity in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The methanolic extract of Leea asiatica leaves produced hepatoprotective activity by lowering the level of serum SGOT, SGPT, ALP, total bilirubin, total cholesterol and triglyceride in acetaminophen-induced experimental model [ 36 ]. An in vivo study conducted by Ajiboye et al., (2014) stated that the aqueous seed extract of Leea guineensis showed hepatoprotective activity against DDVP-induced oxidative stress by altering the levels of increased lipid peroxidation and enhancing decreased activities of antioxidative enzymes such as catalase, superoxide dismutase, and glutathione peroxidase [ 43 ]. In another study, it was found that the methanolic extract of Leea macrophylla leaves partially improved the hepatic damage in CCl 4 -induced Wistar albino rats and prevented oxidative damage as well [ 86 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The methanolic extract of Leea asiatica leaves produced hepatoprotective activity by lowering the level of serum SGOT, SGPT, ALP, total bilirubin, total cholesterol and triglyceride in acetaminophen-induced experimental model [ 36 ]. An in vivo study conducted by Ajiboye et al., (2014) stated that the aqueous seed extract of Leea guineensis showed hepatoprotective activity against DDVP-induced oxidative stress by altering the levels of increased lipid peroxidation and enhancing decreased activities of antioxidative enzymes such as catalase, superoxide dismutase, and glutathione peroxidase [ 43 ]. In another study, it was found that the methanolic extract of Leea macrophylla leaves partially improved the hepatic damage in CCl 4 -induced Wistar albino rats and prevented oxidative damage as well [ 86 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Phenylethyl-rutinoside(41), Icariside D1(42), Hexenylrutinoside(43), Everlastoside C(44) These diglycosidic compounds were identified from methanolic extract of aerial parts of Leea asiatica[35] Bergenin(45), Citroside A(46) These compounds were identified from methanolic extract of aerial parts of Leea asiatica[35] (7S,8R)-9 0 -O-acetylcedrusin (47), (3S,4S)-4-chloro-3hydroxypiperidin-2-one (48) These compounds were isolated from the ethanolic extract of the aerial parts of Leea aequata [39] trans-N-p-coumaroyltyramine (49), N-transferuloyltyramine (50), Vanillic acid (51), Syringic acid (52),α-hydroxyacetovanillone (53), 3,4,5-trihydroxybenzoic acid ethyl ester (54), Isotachioside (55), (6S,9S)-roseoside C (56), Scopoletin (57), 5-hydroxymethylfurfural (58)These compounds were isolated from the ethanolic extract of the aerial parts of Leea aequata[39] Amino Acids, Mucilage's These compounds were identified from aqueous fraction of ethanolic extract of Leea macrophylla root tubers[49] F. Hossain et al Heliyon 7 (2021) e06222…”
mentioning
confidence: 99%
“…Leea guineensis commonly called Red tree vine is an evergreen shrub or small tree that belongs to the family Leeaceae. It is locally called alugbokita and usually propagated by seed or stem cutting; the seed germinates in 14-21 days at 70° F and can grow up to 20ft high; the plant is widely distributed in moist, intermediate temperate zones in tropical Africa including Cote d'Ivoire, Liberia, Sierra Leone, Ghana, Cameroon and Nigeria [18], [19]. The plant is reported to exhibits potential in-vivo anti-tumour and antioxidant activity [20]; while it's antiinflammatory activity was also demonstrated in experimental animals.…”
Section: Introductionmentioning
confidence: 99%
“…Volatile and flammable hydrocarbons are stored in unspeakable places which have often times resulted in terrible fire accidents that brought loss of lives and properties. No wonder that, frequently, there are mass casualty reports in the Nigerian mass media on carbon monoxide poisoning from electrical power generators (Ajiboye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%